The interaction of MD-2 with small molecules in huanglian jiedu decoction play a critical role in the treatment of sepsis - Chen, Guirong; Wang, Xiaobo; Liu, Chang; Zhang, Mingbo; Han, Xueying; Xu, Yubin (Frontiers in Pharmacology, 2022)
Huanglian Jiedu Decoction (HJD) is used for treating sepsis in China. Active components from HJD refer to various active ingredients of HJD, while active component formulation (ACF) refers to the combination of palmatine, berberine, baicalin, and geniposide from HJD according to the quantity of HJD. The detailed mechanisms of the active components from HJD and ACF in sepsis treatment are unclear. Molecular docking, surface plasmon resonance (SPR), ELISA, RT-qPCR, and Western blotting were used to assay the possible mechanism in vitro. The efficacy and mechanism of ACF and HJD were assessed by pharmacodynamics and metabolomics analyses, respectively. The results revealed that palmatine, berberine, baicalin, and geniposide showed good binding capacity to MD-2; decreased the release of NO, TNF-α, IL-6, and IL-1β; inhibited the mRNA expression of iNOS, TNF-α, IL-6, IL-1β, and COX-2; and downregulated the protein expressions of MD-2, MyD88, p-p65, and iNOS induced by LPS; which indicated that they can inactivate the LPS-TLR4/MD-2-NF-κB pathway. Thus, ACF was formed, and the pharmacodynamics assay suggested that ACF can reduce inflammatory cell infiltration and organ damage in accordance with HJD. Furthermore, 39 metabolites were selected and identified and the regulatory effect of these metabolites by ACF and HJD was almost consistent, but ACF might alleviate physical damage caused by HJD through regulating metabolites, such as 3-hydroxyanthranilic acid. ACF could represent HJD as a new formulation to treat sepsis.